2022
DOI: 10.3390/foods11244036
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Conversion of Food Waste to Carbonaceous Solid Fuel—A Review of Recent Developments

Abstract: This review critically discussed recent developments in hydrothermal carbonization (HTC) of food waste and its valorization to solid fuel. Food waste properties and fundamentals of the HTC reactor were also covered. The review further discussed the effect of temperature, contact time, pressure, water–biomass ratio, and heating rate on the HTC of food waste on the physiochemical properties of hydrochar. Literature review of the properties of the hydrochar produced from food waste in different studies shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Hydrothermal carbonization (HTC) is a thermochemical process that is applied at mild reaction temperatures, typically ranging from 180 to 250 • C, with water as the reaction medium [9,10]. The major advantage of this process is the direct applicability of wet (biomass) streams, which excludes the use of an energy-intensive drying step [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrothermal carbonization (HTC) is a thermochemical process that is applied at mild reaction temperatures, typically ranging from 180 to 250 • C, with water as the reaction medium [9,10]. The major advantage of this process is the direct applicability of wet (biomass) streams, which excludes the use of an energy-intensive drying step [11].…”
Section: Introductionmentioning
confidence: 99%
“…The major advantage of this process is the direct applicability of wet (biomass) streams, which excludes the use of an energy-intensive drying step [11]. During the HTC process, multiple reactions take place simultaneously, including hydrolysis, dehydration, decarboxylation, condensation and repolymerization [10,[12][13][14]. The effect of these reactions is a decrease in both the atomic H/C and atomic O/C ratio, moving towards values that are typical for lignite [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] As a new technology, hydrothermal carbonization (HTC) has been shown to be able to improve the fuel quality of biomass while consuming less energy. [5,6] Studies have shown that the reaction temperature is the main factor in HTC [7] ; hemicellulose (decomposed at 180 °C) and cellulose (decomposed at 220 °C) are decomposed into monomers, and the lignin component is more stable at 260 °C. [8,9] Specifically, hemicellulose and cellulose usually decompose completely at treatment temperatures above 230 °C and 270 °C, respectively.…”
Section: Introductionmentioning
confidence: 99%